Development of live feed enrichment product for marine fish larviculture - Vijayagopal, P (Indian Journal of Fisheries, 2012)
Phytoplankton cultures of Nanochloropsis oculata, Isochrysis galbana, Pavlova viridis and Dicrateria inornata, were scaled up and analysed for fatty acids. I. galbana proved the richest source of docosahexaenoic acid (DHA). P. viridis and D. inornata are rich in eicosapentaenoic acid (EPA). N. oculata is rich in EPA and arachidonic acid (ARA). When rotifers were enriched with I. galbana and analysed for fatty acids at specific time intervals, DHA content increased till 30 h with a maximum DHA level of 1.13% obtained in enriched rotifers. Subsequently, development of enriched emulsions using sardine oil (90%) and fish roe (10%) as the major ingredients yielded a DHA content of 39% and EPA content of 17% and was used to enrich rotifers. The resultant enrichment level was 8.76% DHA and 2.35% EPA at six hours after which, a decline in the polyunsaturated fatty acid (PUFA) content was observed. The enrichment formulation holds promise as an import substitute.